Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics

Proteome dataset of Candida albicans (ATCC10231) opaque cell - Zore, Gajanan; Abdulghani, Mazen; Kodgire, Santosh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra (BMC Research Notes, 2024)
<h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 0px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Objectives Candida albicans, a polymorphic yeast, is one of the most common, opportunistic fungal pathogens of humans. Among the different morphological forms, opaque form is one of the least-studied ones. This opaque phenotype is essential for mating and is also reported to be involved in colonizing the gastrointestinal tract. Considering the significance of the clinical and sexual reproduction of C. albicans, we have investigated the morphophysiological modulations in opaque form using a proteomic approach. <h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 24px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Data description In the current investigation, we have used Micro-Liquid Chromatography-Mass Spectrometry (LC-MS/MS) analysis to create a protein profile for opaque-specific proteins. Whole-cell proteins from C. albicans (ATCC10231) cells that had been cultured for seven days on synthetic complete dextrose (SCD) medium in both as an opaque (test) and as a white (control) form cells were extracted, digested, and identified using LC-MS/MS. This information is meant to serve the scientific community and represents the proteome profile (SWATH Spectral Libraries) of C. albicans opaque form.